Organizational Commitment and Performance: The Moderating Role of Transformational Leadership - Damayanti, Ni Nyoman Sri Rahayu; Agung Wira Pertama, I Gde; Budi Anggiriawan, I Putu (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
Individual performance is an important factor that can be a determinant of organizational performance. Individual performance is individual behavior at work that consistently contributes to the achievement of organizational goals. This shows that individual performance is under the individual's control. These conditions make individual performance one of the most important aspects to be traced in various organizations. Likewise in Private Higher Education (PHE) where the performance of employees will also contribute to organizational performance. The high number of PHE is a factor causing high competition between PHE. The novelty of this research is in the development of literature related to organizational commitment and individual performance by including transformational leadership as a moderator. In addition, this research was conducted in universities which have not been followed up much. This research is explanatory research using a survey design. The research samples were employees at Warmadewa University and Pendidikan Nasional University. The data analysis technique used is moderated regression analysis. The results of the study show that organizational commitment has a positive effect on individual performance. Further results show that transformational leadership moderates the relationship between organizational commitment and individual performance.